Pengaruh Pelayanan Prima Terhadap Kepuasan Pelanggan Pembeli Diamond Hago (Studi Kasus Di Galeri Virtual Teknologi) - Nuniek Dewi Pramanik; Elsa Denis Sapitri; Hani Kustyanti Kusnadi; Jusuf Nurdin; Adi Chandra Triana (Journal on Education, 2023)
This study aims to determine the effect of excellent service on customer satisfaction at Gallery Virtual Technology of Bandung. This was a quantitative study and data were collected through questionnaires. The study samples involved 100 diamond customers of hago live streaming application at Gallery Virtual Technology. Based on the results of the study, it was obtained a correlation coefficient of 0.307 (in the range of 0.20-0.399) which indicated a low effect of excellent service on customer satisfaction at Gallery Virtual Technology. The t hypothesis test obtained a t count of 3.191 or higher than t table of 1.660 which meant that there was an effect of excellent service on customer satisfaction at Virtual Technology Gallery. Furthermore, the value of coefficient of determination or R square was 9.4%, which could be interpreted that customer satisfaction at Gallery Virtual Technology was influenced by excellent service by 9.4%. The problem found in this study was regarding the low effect of excellent service on customer satisfaction due to more significant factors. The solution to this problem is by approaching customers to ask certain things as a measure of satisfaction in addition to excellent service.